Politics, religion and violence: the Maccabean Wars - Assmann, Jan (Politics, religion and political theology, 2017)
The world is full of violence committed in the name of religion. Where does this violence come from? What has it to do with religion? This is the question to which this chapter is dedicated. The author examines this question from an Egyptologist’s or antiquarian’s point of view, exploring the earliest occurrences of genuinely religious violence and their historical circumstances.